The meaning of life and life satisfaction among international students at University Putra Malaysia (UPM) during the Covid-19 pandemic - Ab. Razak, Ratna Roshida; Lee, Yok Fee; Mohd Yusoff, Ahmad Nasir; Muhammad, Zarina; Yang, Zhijia (Centre for Promoting Ideas, 2021)
This study is an attempt to examine a sense of existential meaning or meaning of life and life satisfaction among the international students amid a period of volatility, uncertainty, complexity, and ambiguity (VUCA), particularly in light of the tragic COVID-19 pandemic. The participants were 204 international students. They were recruited to respond to two sets of questionnaires namely Meaning in life using (MLQ) developed by Steger (2010) and the Satisfaction with Life Scale (SWLS) was first created by researchers Diener, Emmons, Larsen, and Griffin (1985). The results indicated that a positive relationship was found between meaning in life and life satisfaction among international students during the COVID-19 pandemic. This significant relationship found between the meaning of life and life satisfaction among the international students, could lead them to adjust, embrace and change lives and turn the tragedy into a time of resilience, strength, knowledge and a new environment of mutual and communal living, sharing responsibilities and appreciating solidarity. This finding matches with the previous research that has shown that a capacity to behave with insight and humility while preserving inner and outer harmony irrespective of the circumstances has also been found to be a key component in increasing life satisfaction.